Impact of inspiratory pressure rise time on lung-emptying in time controlled adaptive ventilation - Neetz, Benjamin; Rehn, Patrick; Kraus, Nicole; Schmidt, Werner; Reinhardt, Lars; Flohr, Thomas; Laußer, Christoph; Weigand, Markus A.; Fiedler-Kalenka, Mascha (Respiratory care, 2025)
Background: The airway pressure release ventilation (APRV)-based time controlled adaptive ventilation (TCAV) protocol can potentially minimize ventilator-induced lung injury (VILI). Inspiratory pressure rise time (IPRT) is a parameter available in pressure-controlled ventilation modes, yet its role within TCAV remains unclear. We hypothesized that varying IPRTs impact lung emptying and associated ventilatory parameters (driving pressure [ΔP], intrinsic PEEP [PEEPi], exhaled tidal volume [VTe]). - Methods: This single-center, prospective exploratory study included 10 intubated subjects ventilated utilizing the TCAV protocol. Subjects underwent consecutive experimental trials with IPRTs of 500 and 1,000 ms, each preceded by a baseline (BL) with an IPRT of 0 ms. Analyzed parameters were ventilator-derived ΔP (ΔPvent), PEEPi, and VTe. Elastance (ERS = ΔPvent/VTe) and elastance-derived ΔP (ΔPelast = ERS × VTe) were calculated. End-expiratory lung volume (EELV) and end-inspiratory lung volume were assessed through electrical impedance tomography (EIT). - Results: Prolonged IPRT increased ΔPelast compared with ΔPvent in each baseline/trial combination (ΔPvent 13.5 ± 1.5 cm H2O vs ΔPelast 18.4 ± 2.7 cm H2O at 1,000 ms IPRT, P < .001) through a loss of PEEPi. Conventional PEEPi measurements did not detect these changes. The EIT data showed a reduction in EELV during the trials. - Conclusions: IPRT prolongation under TCAV reduced EELV/PEEPi, therefore increasing ΔP. Conventional PEEPi measurement methods are misleading in this context. We therefore suggest adding the recommendation to set IPRT to 0 ms for the TCAV protocol.
Online veröffentlicht: 25. August 2025
Gesehen am 17.12.2025